2020
DOI: 10.1017/s0007114520001695
|View full text |Cite
|
Sign up to set email alerts
|

Are the nutrient and textural properties of Australian commercial infant and toddler foods consistent with infant feeding advice?

Abstract: Infant feeding guidelines worldwide recommend first foods to be Fe rich with no added sugars and that nutrient-poor discretionary foods are to be avoided. Feeding guidelines also recommend exposing infants to a variety of foods and flavours with increasingly complex textures. Here, we compare nutritional and textural properties of commercial infant and toddler foods available in Australia with established infant feeding guidelines. Nutrition information and ingredient lists were obtained from food labels, manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 20 publications
5
35
1
Order By: Relevance
“…An associated issue that requires consideration in any oral health strategy aimed at young children today is the recent exponential growth of the Australian baby food industry [ 48 ]. The market is increasingly flooded with sugar rich infant and toddler products, with the majority of ‘pouch foods’ increasingly available in the supermarket being predominantly sweet [ 49 ]. Although these foods were not discussed in the reviewed articles, perhaps because of their recent establishment in the baby and toddler food market, their sugar content is concerning given the well-established links to dental caries44.…”
Section: Discussionmentioning
confidence: 99%
“…An associated issue that requires consideration in any oral health strategy aimed at young children today is the recent exponential growth of the Australian baby food industry [ 48 ]. The market is increasingly flooded with sugar rich infant and toddler products, with the majority of ‘pouch foods’ increasingly available in the supermarket being predominantly sweet [ 49 ]. Although these foods were not discussed in the reviewed articles, perhaps because of their recent establishment in the baby and toddler food market, their sugar content is concerning given the well-established links to dental caries44.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that this type of marketing may diminish the value of home meals and work to persuade parents that costly commercial foods are essential [33]. Recent research on the nutritional and textural composition of CCF available for sale in Australia demonstrates their unsuitability as a primary food source, being predominantly sweet flavored, low in iron, snack foods that would be classified as noncore, or discretionary items, and purees lacking appropriate textural variety [15,36]. The importance of texture in the development of skills is utilized in marketing by brands promoting the value of their snack products in self-feeding and of attributes such as "tongue lateralization", which encourages the perception that these products are necessary for optimal child development.…”
Section: Discussionmentioning
confidence: 99%
“…Regular inclusion of cows milk, wheat, hen's egg, peanut, tree nuts, fish, shellfish, soy, sesame and lupin containing foods make important contributions to infant nutrition, including contributing to diet diversity which has been linked to improved future health outcomes, including reduced allergic diseases. 17 While several reviews have focussed on nutritional, textural and flavour analysis of weaning foods in Australia, 18 the UK 19 and in the USA, 20 we are not aware of any other systematic analysis of the allergen content of weaning foods. The recent review of the nutritional content of UK weaning foods included an ingredient listing, surveillance of which indicates that weaning foods available in the UK are also low in common allergens.…”
Section: Discussionmentioning
confidence: 99%